A brain abscess complicating the clinical profile of opioid withdrawal delirium: a case report - Kul, Müslüm; Savaş, Haluk A.; Kaya, M. Cemal; Selek, Salih; Yumru, Mehmet (Journal of Dependence, 2008)
Delirium is an important problem which is commonly encountered by physicians from all fields and it can inflict negative effects over the patient’s general profile when not appropriately treated. It may occur due to numerous reasons. While in some cases a single cause can play a role in its development, in certain cases multiple etiologies may be present as well. Multiple etiologies occurs especially in patients who are old and hospitalized. However, in practice, presence of multiple factors is oftenly overlooked. Inappropriate etiological evaluation delays the treatment and contributes to elevation of mortality and morbidity. Thus, it should be always kept in mind that in delirium patients, more than one factor causing the disease can be present. In the present report, a delirium case with combined opioid withdrawal and brain abscess, has been presented in order to emphasize the possibility of presence of multiple etiologies.
Keywords: Delirium; brain abscess; opioid withdrawal; multiple etiologies